Semʹâ i vospitanie detej v religioznom diskurse arhiepiskopa Simferopolʹskogo i Krymskogo Luki - Gadomskaâ, Galina P. (Stylistyka, 2020)
During four decades of his service in the Church, Valentin Felixovich Voino-Yasenetsky (Archbishop Luke of Simferopol and Crimea) delivered numerous sermons, most of which were recorded. Later, they began to appear in the form of publications and became the object of research by representatives of various scientific disciplines. In his sermons, apart from other issues, the preacher paid special attention to the family and education of the younger generation. This article is an attempt to analyze the religious discourse of the Archbishop, using the example of the sermon “On the family and education of children”, delivered by him on 13 October 1947. The author of the sermon adheres to the traditional point of view on marriage and raising children. And this can be confirmed not only by the texts of his sermons, but also by the lifepath the preacher took himself. In this text, Archbishop Luke, in the classical tradition of quotations from the Bible, expresses his attitude towards the issues raised and offers solutions to them. If we take into account the processes going on in the modern world (new views on the institution of marriage, devaluation of marriage and the family, the reluctance of parents to take care of their own children, shifting of responsibility for raising children to other people or state institutions and organizations), it should be noted that, despite the fact that the sermon was delivered more than 70 years ago, it has not lost its relevance and can serve as a reference book for spouses and parents, as revealed by the analysis of the preacher’s discourse. Taking into account the peculiarities of the analyzed genre, the author of this article attempts to look at the text of the sermon from the theolinguistic perspective and, consequently, applies the theolinguistic approach in the process of its analysis and description.